Thermal light correlations e ects on light harvesting performance (2016)
Thermal light is the kind of radiation that naturally feeds the light-harvesting processes on Earth, either natural or artificial. It can be completely described by using three properties: intensity, spectrum, and correlations. Although we understand how photoreceptor structures respond to different light intensities and spectra, too few is known about how thermal light correlations affect the performance of different light-harvesting structures. For this reason, the main goal of our work is to identify the advantages that thermal light correlations offer for efficiency improvement in low intensity exposure and photo-protection in high intensity exposure. In this vein, we search for the effects of thermal light spatial and temporal correlations on both photosynthesis and artificial systems. Particularly in bacterial photosynthesis, we look for an adaptive relationship between the photosynthetic mechanisms present in Purple bacteria and the properties of the thermal light that feeds it. In the case of arti cial light collection, we aim to nd appropriate detection schemes that lead to an e ciency improvement when the spatial and temporal correlations of the light are detected by the system. To this end, we employ the generating functional formalism as the statistical basis for simulating detection events of the incoming light with any degree of spatio-temporal coherence (ranging from the Poissonian to Bose-Einstein distributions). This formalism provides the statistical framework to understand the role of intensity and correlations on the photoreception's behaviour for harvesting structures adjusted to speci c frequency ranges of the spectrum. All the mathematical framework was accomplished with actual photosynthetic parameters to simulate light reception and all the stages for adenosine triphosphate (ATP) production in photosynthesis; but also applied in the search for thermal light advantages in arti cial light harvesting systems. For bacterial photosynthesis, we found that the spatio-temporal correlations of thermal light are perceived and are responsible for photo-excitations dissipation in the high intensity regime, giving a possible new channel for excess energy dissipation. In the case of arti cial light harvesting, we conclude that correlations improve efficiency and stability of the obtained currents and we also found that dense-symmetric spatial con gurations of detectors raise the detection probabilities.